Primary Liver Lymphoma Presenting as Liver Nodules - Silva,João Manuel (2021)
Abstract: The liver is usually affected in advanced stages of lymphoproliferative diseases, but primary liver lymphomas (PLLs) are rare. The diagnosis is usually late, especially in patients without identifiable risk factors, with consequent worse prognosis. We report the case of a 59-year-old female with progressive worsening pain in the right hypochondrium and weight loss. She was previously healthy and had a family history of gastrointestinal and gynecologic neoplasms. During the initial investigation, three liver nodules suggestive of liver metastases were found. Nevertheless, no primary neoplasm was identified in a subsequent evaluation with imaging and endoscopic exams. Laboratory exams excluded hepatic infections, metabolic diseases, and acquired immunosuppression. Biopsy of the lesions revealed diffuse large B-cell lymphoma. Lymph node and medullar involvement were excluded, and the diagnosis of PLL was assumed. The patient started chemotherapy with R-CHOP. With this case, we intend to alert for this differential diagnosis of liver nodules, even in the absence of predisposing conditions for lymphoma. We point out the need to define universal diagnosis criteria for this pathology.